Exploring Parabolas, Ellipses, and Hyperbolas in Space and their Applications in Various Sciences (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This work focuses on a detailed study of the properties of conic sections, namely parabolas, ellipses, and hyperbolas, as well as an analysis of their applications in various sciences.